DOSIS BIOCHAR DIPERKAYA SILIKA DAN ARANG AKTIF DALAM PERBAIKAN KAPASITAS MEMEGANG AIR, C-ORGANIK DAN KAPASITAS TUKAR KATION PADA INCEPTISOL - Islamiati, Annisa; Citraresmini, Ania; Tamad, Tamad (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Inceptisol is a widespread soil with a total of 37% of the land area in Indonesia. On the island of Java, Inceptisol has an intensive management intensity, one of which is in Kertasari District, Bandung Regency, West Java, which has a high potential for soil damage due to a decrease in the soil's ability to hold water. Biochar enriched with silica and activated charcoal Oil Palm Empty Fruit Bunches (OPEFB) is a type of organic soil amendment that can improve the ability of Inceptisol to hold water and support nutrient needs through organic C indicators and cation exchange capacity. The research was carried out by taking soil samples and then incubating them according to the treatment for 14 days. The experimental design used in the study was a non-factorial, Completely Randomized Design (CRD) method with 12 levels consisting of 3 L/ha of silica-enriched rice husk biochar and OPEFB's activated charcoal, with each in the range of 0-6.25 tons/ha. Measurement results of water holding capacity parameters, C-organic, and cation exchange capacity were analyzed statistically, and significant differences in responses were obtained from the treatments. The optimum dose for Inceptisol in Kertasari uses silica-enriched biochar to increase water holding capacity, organic C, and cation exchange capacity, respectively, at 4.92 tons/ha, 5.73 tons/ha, and 2.51 tons/ha. Otherwhile, OPEFB's activated charcoal was 1.7 tons/ha, 0.125 tons/ha, and 1.5 tons/ha, respectively.